2010
DOI: 10.1002/art.27466
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized, prospective, placebo‐controlled trial of bosentan in interstitial lung disease secondary to systemic sclerosis

Abstract: Objective. Endothelin is implicated as a participatory pathway in systemic sclerosis (SSc). We tested this hypothesis in a 12-month trial of bosentan, a nonselective endothelin receptor antagonist, as a therapy for SSc-related interstitial lung disease (ILD).Method. Patients with SSc and significant ILD were recruited to this prospective, double-blind, randomized, placebo-controlled, parallel group study. The inclusion criteria were designed to select a cohort enriched for patients with active and progressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(74 citation statements)
references
References 30 publications
3
70
0
1
Order By: Relevance
“…In the 163 patient study, the drug failed to demonstrate a difference in the primary endpoint of a change in six-minute walk distance. Secondary end points of time to death and worsening of PFTs were also no different [55]. This negative study mirrors negative results seen in trials of endothelin receptor antagonists in IPF [56].…”
Section: Other Therapiessupporting
confidence: 68%
“…In the 163 patient study, the drug failed to demonstrate a difference in the primary endpoint of a change in six-minute walk distance. Secondary end points of time to death and worsening of PFTs were also no different [55]. This negative study mirrors negative results seen in trials of endothelin receptor antagonists in IPF [56].…”
Section: Other Therapiessupporting
confidence: 68%
“…Whereas significant improvements in functional class and hemodynamics were observed in the overall cohort of 49 patients, no clear benefits were observed among the 13 subjects with combined PH-ILD (11). Moreover, bosentan was not beneficial in SSc-ILD without PH (38).…”
Section: Discussionmentioning
confidence: 80%
“…A smaller, more recent study of nine SSc-ILD patients also failed to demonstrate improvement in lung function or imaging after two years of bosentan treatment [27]. Patient selection might explain some of the negative results reported with bosentan, particularly in the latter trial where all the patients had severely impaired lung function, long disease duration and had demonstrated relapse after cyclophosphamide therapy [27]. In addition to patient selection, other factors such as primary endpoint selection might also have influenced the results.…”
Section: Rheumatologymentioning
confidence: 93%
“…Unfortunately, neither trial demonstrated efficacy of bosentan, although there did appear to be a trend in favor of bosentan delaying the time to death or disease progression in patients with biopsy-proven usual interstitial pneumonia [26]. A smaller, more recent study of nine SSc-ILD patients also failed to demonstrate improvement in lung function or imaging after two years of bosentan treatment [27]. Patient selection might explain some of the negative results reported with bosentan, particularly in the latter trial where all the patients had severely impaired lung function, long disease duration and had demonstrated relapse after cyclophosphamide therapy [27].…”
Section: Rheumatologymentioning
confidence: 99%
See 1 more Smart Citation